Study on the Effect of Geopolymer Concrete in Reducing Carbon Footprint - Darshan Rasikbhai Sorathiya; Parikshit Khoker; Rishabh Sain (Marasofi International Media and Publishing (MIMP), 2025)
The construction industry is one of the largest contributors to global CO₂ emissions, primarily due to the production of Ordinary Portland Cement (OPC). In recent years, geopolymer concrete (GPC) has emerged as a promising sustainable alternative, utilizing industrial by-products such as fly ash and ground granulated blast furnace slag (GGBFS) to replace traditional cement. This study investigates the effectiveness of geopolymer concrete in reducing the carbon footprint of concrete production without compromising structural performance. A series of experimental tests were conducted to compare the mechanical and environmental properties of GPC with conventional OPC concrete, including compressive strength, durability under aggressive environments, and total embodied carbon emissions. Results showed that geopolymer concrete achieved comparable or superior compressive strength values at 28 days, particularly when heat curing was applied. Furthermore, a significant reduction of up to 80% in CO₂ emissions was observed, depending on the source material and mix design. The study confirms that geopolymer concrete has strong potential to be adopted in both structural and non-structural applications, particularly in regions with abundant industrial waste materials. It is recommended as a key strategy in decarbonizing the construction sector while meeting performance and durability requirements.